Zur Abgrenzung von Abfall und Produkt bzw. Rohstoff. - (:unkn) unknown (Nomos, 2005)
EuGH, Urteil vom 11. November 2004 - C-457/02 - Antonio Niselli. difu
Keywords: Abfallrecht; Abfallverwertung; Entsorgung; Abfallwirtschaft; Europarecht; Abfall; Rohstoff; Produkt; Abfallbegriff; Abgrenzungskriterium